Influence of Job Satisfaction on Affective Commitment Among Bank Employees - Asaari, Muhammad Hasmi Abu Hassan; Anuar, Noor Awatis (Fakulty of Social and Political Science, Hasanuddin University, 2016)
This paper explores !he influence of job satisfaction towards level of affective commitment among bank employees. Influence of job satisfaction can be related to what the erripJoyees like or inspire quality that lies within bank employees that will lead to higheratfective commitment. It is extremely important for bank employees to have high level of job satisfaction in order for the bank: to have high productivity of employees and at the same time maintain the service standard as majority of the are facing customers on their day-to-day banking operations. Banking services is built on trust and also the level of standard etiquette provided by the bank. employees and the standard banking operations itself. Banks in Malaysia still usc employccs' functions to catcrthcir services to customers. In certain countries, the bank employees' usage is very minimal as compared to Malaysia's banking sector. Moreover, bank employees are very essential to the banking service since majority of them perfonn banking duties, credit administrntion. and' call centerpersonnels. Questionnaires were handed to bank employees in the northern states of Malaysia and were analysed using SPSS. Bank employees indicated job satisfaction was associated with their affective commitment. These findings further have an impact on bank employees and banks' top management.